Green chemistry and engineering : a pathway to sustainability - Marteel-Parrish, Anne.; Abraham, Martin A., 1961- (Hoboken, New Jersey : Wiley, 2014)
'Although many were skeptical of the green chemistry movement at first, it has become a multimillion-dollar business. In preventing the creation of hazardous wastes, laboratories and corporations can save millions in clean up efforts and related health costs. This book supplies students with concepts commonly taught in undergraduate general chemistry and general engineering courses, but with a green perspective. It is unique in presenting an integrated discussion of green chemistry and engineering from first principles - not as an afterthought. Real-world examples show creative problem solving based on the latest issues'--
'This book presents the same concepts commonly taught in undergraduate general chemistry and general engineering courses (organic, inorganic, analytical, and biochemistry, with applications to environmental and materials science) but with a green perspective'--
10.5 incorporation of green chemistry in process design for sustainability10.6 case studies demonstrating the economic benefits of green chemistry and design; 10.7 summary; references; 11 green chemistry and toxicology; 11.1 introduction; 11.2 fundamental principles of toxicology; 11.3 identifying chemicals of concern; 11.4 toxicology data; 11.5 computational toxicology and green chemistry; 11.6 applications of toxicology into green chemistry initiatives; 11.7 future perspectives; references; index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Green chemistry; Química ambiental; Desenvolupament sostenible; Electronic books; Electronic books